Coordination of Chromosome Segregation and Cell Division in Staphylococcus aureus - Bottomley, Amy L.; Liew, Andrew T. F.; Kusuma, Kennardy D.; Peterson, Elizabeth; Seidel, Lisa; Foster, Simon J.; Harry, Elizabeth J. (Frontiers in Microbiology, 2017)
Productive bacterial cell division and survival of progeny requires tight co-ordination between chromosome segregation and cell division to ensure equal partitioning of DNA. Unlike rod-shaped bacteria that undergo division in one plane, the coccoid human pathogen Staphylococcus aureus divides in three successive orthogonal planes, which requires a different spatial control compared to rod-shaped cells. To gain a better understanding of how this co-ordination between chromosome segregation and cell division is regulated in S. aureus, we investigated proteins that associate with FtsZ and the divisome. We found that DnaK, a well-known chaperone, interacts with FtsZ, EzrA and DivIVA, and is required for DivIVA stability. Unlike in several rod shaped organisms, DivIVA in S. aureus associates with several components of the divisome, as well as the chromosome segregation protein, SMC. This data, combined with phenotypic analysis of mutants, suggests a novel role for S. aureus DivIVA in ensuring cell division and chromosome segregation are co-ordinated.